PENGARUH MOBILE HEALTH E-SERVICE QUALITY PADA KEPUASAN PELANGGAN DAN KEPERCAYAAN PELANGGAN SERTA KELANJUTAN PENGGUNAANNYA DI ERA PANDEMIK COVID-19 - Ripka Renaldi; Christabella Monica; Paul Lumbantobing (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
mHealth application has rapidly gained its popularity since the COVID-19pandemic stroke the world. Looking at its promising future in function and variousadvantages, we conducted a study to observe the effect of e-service quality oncustomer satisfaction, customer trust, and subsequently customer retention. Thisstudy uses quantitative method, the population is users of mobile healthapplications who are of productive age. The sampling technique used is simplerandom sampling with the criteria of respondents who have used the mHealthapplication as many as 149 respondents. From the results of our study, it wasfound that e-service quality has a positive relationship with customer satisfactionand trust, customer satisfaction and trust have a positive relationship withcustomer retention. However, e-service quality does not have a direct relationshipwith customer retention. This may be influenced by application factors that oftencrash or user doubts about their privacy when providing information inapplications, as well as comparisons between applications in terms of price andquality of service.